Implementing quality function deployment using service quality and Kano model to the quality of e-learning - Theresiawati Theresiawati; Henki Bayu Seta; Artika Arista (International Journal of Evaluation and Research in Education (IJERE), 2023)
E-learning has become an important aspect of university education. System evaluation must be carried out by higher education management to identify the number of e-learning successes and future improvement efforts. Three research methodologies were used in this study to measure, classify, and translate service quality into an improvement process, namely SERVQUAL, Kano model, and quality functional deployment (QFD). A survey involving 219 UPN “Veteran” Jakarta students as e-learning users were done to examine the developed methodology. The partial least square (PLS) method was used to process the data. This study employed the quantitative method. Website content, assurance, empathy, responsiveness, tangibles, reliability, and learning content are variables in this approach. This study provided knowledge on identifying and analyzing the quality of e-learning services using the service quality (SERVQUAL) method by calculating the score gap between the perceived service quality assessment (performance) and the expected service quality using website content, assurance, empathy research variables, responsiveness, tangibles, reliability, learning content, e-learning quality, satisfaction, and behavioral intention. This study also evaluates what improvements can be made to improve the quality of e-learning services.